The Influence Of Customer Review, Customer Rating, And Celebrity Endorser On Repurchase Intention With Hedonic Shopping Value As A Moderator - Triscna Juwita; Vikki Winardi (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study. aims to analyze the effect of Customer Review, Customer Rating, and Celebrity Endorser on Repurchase Intention with Hedonic Shopping Value as a moderating variable. This study uses quantitative methods by collecting data through surveys to 150 respondents who have purchased products online. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results showed that Customer Review,. Customer Rating, and Celebrity Endorser have a positive and significant influence on Repurchase Intention. In addition, the moderating variable Hedonic Shopping Value has a different effect on the relationship between variables. Hedonic Shopping Value strengthens the relationship between Customer Rating and Celebrity Endorser on Repurchase Intention, but weakens the relationship between Customer Review and Repurchase Intention. The findings indicate that customer reviews, ratings and celebrity endorsements play an important role in influencing consumers' repurchase intentions, especially for those with high hedonic values. Companies are advised to improve marketing strategies through managing customer reviews and ratings and selecting celebrity endorsers that are relevant to the target market. This research also contributes to the development of literature related to consumer behavior and digital marketing.